Effect of Entrepreneurial Marketing Practice on Performance of Small and Medium Agro Based Youth Enterprises in Kenya (International Journal of Scientific Research and Management (IJSRM), 2024)
The research aimed to analyze the effect of entrepreneurial practices on the success of small and medium agro-based youth entrepreneurs in Kenya. The research aimed to examine the effect of entrepreneurial marketing on the performance of small and medium-sized agro-based youth entrepreneurs in Kenya. This study used a mixed research design, using both quantitative and qualitative methodologies. The research focused on small and medium-sized agricultural youth entrepreneurs in Kenya, namely in Trans Nzoia, Kakamega, and Bungoma Counties. These counties were represented by the Kiminini, Nzoia, and Ndalu wards, respectively. There are a total of 48 agro-based youth small and medium enterprises (SMEs) registered in these wards, consisting of 1,500 individuals between the ages of 18 and 35. The research has a sample size of 306 respondents. This research used a two-step sample approach, starting with stratified sampling followed by simple random sampling. The research used structured questionnaires as the primary means of gathering data. The research used descriptive statistics, namely frequencies and percentages. The use of inferential statistics, such as correlations and regression, was implemented. The results demonstrated that entrepreneurial marketing practice has a favorable and substantial impact on the performance of small and medium agro-based youth firms in Kenya. The study further recommends that the government should prioritize support for MSMEs to buttress their marketing functions through reduction of the chargeable tariffs, levies and licenses and installation of relevant Internet infrastructure and capacity building so as to enhance their performance.